Lithological features of hydrate-bearing sediments and their relationship with gas hydrate saturation in the eastern Nankai Trough, Japan. (September 2015) - Ito, Takuma; Komatsu, Yuhei; Fujii, Tetsuya; Suzuki, Kiyofumi; Egawa, Kosuke; Nakatsuka, Yoshihiro; Konno, Yoshihiro; Yoneda, Jun; Jin, Yusuke; Kida, Masato; Nagao, Jiro; Minagawa, Hideki
Abstract: Gas hydrate-bearing sediments from the eastern Nankai Trough, Japan, are characterized in terms of their lithology, interpreted processes and paleoenvironments of deposition, and various geometric parameters of their grain size distribution. These data are used to determine the relative influence of each characteristic on gas hydrate saturation within the sedimentary column. Four lithologies have been identified in a single turbidite sequence that can be attributed to hyperpycnal flow deposits, Tc or Td divisions of a turbidite sequence, a Te division of a turbidite sequence, and hemipelagic mud. Facies association indicates that the sediment core can be vertically divided into units that are characteristic of three depositional environments: a lowermost channel-fill turbidite sequence, an intervening sheet-like turbidite sequence, and an uppermost basin floor sequence. The channel-fill turbidite and sheet-like turbidite sequences are the best hydrate reservoirs, as evidenced by the high levels of gas hydrate contained within them. The relationships between gas hydrate saturation and the grain size distribution parameters of median grain size, sand content, and skewness show that the latter can be useful tools with which to assess the quality of the gas hydrate reservoir in the eastern Nankai Trough area. This result provides useful criteria for assessing reservoir quality in the eastern Nankai Trough area. Highlights: We document gas hydrate-bearing sediment core from the eastern Nankai Trough, Japan. Core contains channel-fill turbidite, sheet-like turbidite, and basin floor units. Relationships between gas hydrate content, median grain size, sand content, and skewness are established.